Guanosine‐5′‐Monophosphate Polyamine Hybrid Hydrogels: Enhanced Gel Strength Probed by z‐Spectroscopy. Issue 32 (22nd May 2017) - Belda, Raquel; García‐España, Enrique; Morris, Gareth A.; Steed, Jonathan W.; Aguilar, Juan A.
Abstract: The self‐assembling tendencies of guanosine‐5′‐monophosphate (GMP) can be drastically increased using polyamines, with potential applications in the production of biocompatible smart materials, as well as for the design of antitumor drugs based on G‐quadruplex stabilization. Results from scanning electron microscopy (SEM), wide angle X‐ray scattering (WAXS), rheology, and nuclear magnetic resonance (NMR) z ‐spectroscopy studies are presented. Abstract : Some self‐assembly required : The self‐assembling tendencies of guanosine‐5′‐monophosphate (GMP) can be drastically increased using polyamines, with potential applications in the production of biocompatible smart materials, as well as in the design of antitumor drugs based on G‐quadruplex stabilization.